1997
DOI: 10.1042/cs0920087
|View full text |Cite
|
Sign up to set email alerts
|

Plasma RRR-α-tocopherol Concentrations Are Lower in Smokers Than in Non-Smokers after Ingestion of a Similar Oral Load of this Antioxidant Vitamin

Abstract: 1. Using deuterium-labelled alpha-tocopherol (vitamin E), the plasma kinetics of alpha-tocopherol derived from supplemental RRR-alpha-tocopherol and RRR-alpha-tocopheryl acetate were determined in asymptomatic individuals who smoke and, for comparison, in a group of healthy non-smokers. 2. Venous blood samples were withdrawn 6, 12 and 27 h after the oral administration of a gelatin capsule containing an equimolar mixture of RRR-alpha-tocopheraol and RRR-alpha-tocopheryl acetate. Plasma concentrations of endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Previous studies have consistently shown lower levels of certain plasma antioxidants in smokers (Dietrich et al, 2003) and increased levels of oxidative products such as F 2 -isoprostanes (Morrow et al, 1995). However, the effects of smoking on vitamin E status is less clear, with some studies having observed comparable circulating levels (Lykkesfeldt et al, 2000) while others reporting decreased concentrations in smokers relative a non-smoking groups (Munro et al, 1997). We have shown recently that smokers have decreased a-tocopherol levels in lymphocytes and platelets even though plasma levels were similar to non-smokers (Jeanes et al, 2004b).…”
Section: Bioavailability Of A-tocopherol In Smokersmentioning
confidence: 95%
“…Previous studies have consistently shown lower levels of certain plasma antioxidants in smokers (Dietrich et al, 2003) and increased levels of oxidative products such as F 2 -isoprostanes (Morrow et al, 1995). However, the effects of smoking on vitamin E status is less clear, with some studies having observed comparable circulating levels (Lykkesfeldt et al, 2000) while others reporting decreased concentrations in smokers relative a non-smoking groups (Munro et al, 1997). We have shown recently that smokers have decreased a-tocopherol levels in lymphocytes and platelets even though plasma levels were similar to non-smokers (Jeanes et al, 2004b).…”
Section: Bioavailability Of A-tocopherol In Smokersmentioning
confidence: 95%
“…This is consistent with the observation that smokers have lower antioxidative capacity, likely due to reduced circulating antioxidants (such as a-tocopherol and ascorbic acid) and increased free radical levels than nonsmokers. 4,5) Therefore, the supplement of antioxidants was not as effective in smokers as in nonsmokers. Although the antioxidative effect of adlay was not as strong as that of BL, the current finding that adlay showed an antioxidative effect was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…4) Ascorbic acid and possibly tocopherols have a high turnover in smokers, which can promote the development of the atheromatous plaque. 5) Young barley leaf extract (BL) is a good natural source of vitamins and minerals. It is made from barley leaves harvested 2 weeks after seeding.…”
mentioning
confidence: 99%
“…Reactive oxygen species are generated through various metabolic processes and destroyed by antioxidants, including vitamins A, C, and E, otherwise they are likely contributing to the development of cancer, heart disease, and cataracts [30]. Oxidants also speed up blood vessel damage due to atherosclerosis [31].…”
Section: Effects On the Metabolic Systemmentioning
confidence: 99%